2010
DOI: 10.1038/ejcn.2009.160
|View full text |Cite
|
Sign up to set email alerts
|

Dietary energy density as a marker of dietary quality in Swedish children and adolescents: the European Youth Heart Study

Abstract: Objective: To investigate if dietary energy density is associated with measures of dietary quality (food group, micronutrient and macronutrient intakes) in children and adolescents. Subjects/Methods: In all, 551 children (mean age 9.6 years, 52% girls) and 569 adolescents (15.5 years, 55% girls), sampled from schools in Sweden, completed a single 24-h dietary recall. Dietary energy density (kJ/g) was calculated as the energy from all food consumed divided by the weight of all food consumed. Beverages were excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 38 publications
6
32
0
7
Order By: Relevance
“…The average intake for saturated fats in this Swedish population is higher than that obtained by us (12 %); as for the sugar intake, this is below the average intake in our study (17.22 % in women and 16.43% in men). If differences between averages seem relatively small, what differs by far more is the percentage of those who comply with the recommendations of a healthy diet: thus, in the Swedish study, 30% of the teenagers comply with diet recommendations in respect to saturated fats intake and 82% for the intake of sugar [13] as compared to 3% and 30% respectively from the group we studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average intake for saturated fats in this Swedish population is higher than that obtained by us (12 %); as for the sugar intake, this is below the average intake in our study (17.22 % in women and 16.43% in men). If differences between averages seem relatively small, what differs by far more is the percentage of those who comply with the recommendations of a healthy diet: thus, in the Swedish study, 30% of the teenagers comply with diet recommendations in respect to saturated fats intake and 82% for the intake of sugar [13] as compared to 3% and 30% respectively from the group we studied.…”
Section: Discussionmentioning
confidence: 99%
“…In order to compare it with a population from a similar age group, we used the results of a Swedish study performed on teenagers by Patterson et al [13]. This study reported an average intake of saturated fats of 14.1% and of sugar of 12.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Konsumsi energi, gula, dan lemak jenuh yang berlebih namun rendah konsumsi buah, dan sayur dapat menunjukkan kualitas konsumsi yang rendah. Kualitas konsumsi yang baik dikaitkan dengan tingginya konsumsi buah dan sayur yang memiliki densitas energi rendah serta mencukupi kebutuhan makronutrien secara tepat (Patterson 2010). Rasa yang manis dan gurih menjadikan makanan dan minuman manis dan tinggi lemak lebih banyak disukai oleh masyarakat dibandingkan dengan makanan kaya zat gizi seperti sayur dan buah sehingga konsumsi dari makanan tersebut menyebabkan gizi lebih.…”
Section: Pendahuluanunclassified
“…No entanto, como padrões de consumo são culturalmente determinados, o uso desses métodos torna difíceis as comparações entre estudos em populações distintas e ao longo do tempo. Nesse sentido, a medida da densidade energética da dieta poderia superar essa dificuldade, além de ser mais fácil de calcular (21,30). Dos fatores sociais, demográficos, de estilo de vida e antropométricos investigados, apenas a idade e o hábi-to de fumar associaram-se, negativamente, à densidade energética.…”
Section: Casuística E Métodosunclassified